The Lotus-in-the-Mud Phenomenon: Self-efficacy and Protective Factors in Resilient Children - Swayam Prabha Satpathy (International Journal of Advanced Science and Technology, 2020)
In a plural society like India, a significant proportion of children live in slums and are deprived of enriching experiences. However, some children evince growth despite adversity. Past studies have indicated that resilience is a positive combination of three resources (I have, I am, and I can). The present investigation was geared to identify protective mechanisms (I have) and self-efficacy. It was hypothesized that resilient children have greater self-efficacy than non-resilient children. The screening of resilient children was carried out with the help of teachers and peers. Teachers from various high schools in the city of Bhubaneswar (located in Odisha – an eastern state of India Union) were asked to identify resilient children in their class. Each teacher was also asked to rate his/her nominated child on several dimensions of resilient behaviour. Peers were also asked to rate the same child on these dimensions of behaviour. The congruence of high ratings was used to identify resilient children. Fifteen boys and 15 girls were thus selected. From similar locations, 60 children (30 boys and 30 girls) were randomly sampled to constitute the non-resilient groups.  During the second phase of the study, all children were administered measures of self-efficacy (general and domain-specific), and measure of protective support system. The results indicated greater domain-specific efficacy of resilient children. As hypothesized resilient children indicated greater need for  expression and satisfaction outside their family. The possibility of transplantation of these mechanisms in other disadvantaged children was discussed.